Study on mechanism of bubble growth within a water droplet under rapid depressurization. (April 2018) - Liu, Lu; Ma, Wenjing; Liu, Yixin; Cui, Jingge
Highlights: Bubble growth process within a water droplet under pressure drop was recorded. Bubble growth induced by mass diffusion is much slower than that by superheating. Bubble growth experiences initial stage, transition stage and accelerating stage. Pressure difference, surface tension and friction resistance affect bubble growth. Abstract: This paper reports an experimental and numerical study on mechanism of bubble growth within a water droplet under rapid depressurization. During the experiments, a distilled water droplet was suspended on a thermocouple, which was also used to measure the droplet temperature. A high speed camera was applied to record the bubble expansion. Two mathematical models were developed to describe the bubble growth process. The mass diffusion model considered the bubble growth related to the mass diffusion of nitrogen dissolved in the droplet during pressure drop, and the model was based on the momentum equation of bubble growth coupling with the diffusion equation within the liquid phase. The heat transfer model considered that the droplet superheating resulted in bubble growth. Both of the models considered the influence of thermocouple suspension mode on bubble growth, and a simplified treatment was applied by introducing a friction coefficient. During our experiments, the duration times for bubble growth were mostly 4–8 ms. The verification of mathematical models was achieved by comparing the numerical results with the experimental data. The result shows that the numerical bubble radii calculated by the heat transfer model agree well with the experimental measurement. Through numerical calculations, the factors of pressure difference, droplet diameter and thermocouple suspension mode on bubble growth were analyzed. The results provide insight into the dynamic of bubble growth within a water droplet under rapid depressurization.